APLIKASI PLC SEBAGAI PENGATUR ARAH PUTARAN MOTOR DC UNTUK MENGGERAKAN PMS PADA MINIATUR GARDU INDUK - Aripin, Syarif; Moediyono, Moediyono (Vocational School Diponegoro University, 2013)
Syarif Aripin, Moediyono, in this paper explain that experiment PLC module is a module that consists of modules and visual experiments. This experimental module consists of PLC (Programmeble Logic Controller) which contained PLC in Central Processor Unit (CPU), memory such as RAM (Radom Access Memory), EPROM (Erasable Programmable Only Memory), EEPROM (Electrical Erasable Programmeble Read Only Memory), input-output module and power supply units (Power supply). PLC is used as props in a series of applications to set the dc motor speed desired by mengguanakan input of the switch. OMRON PLC used is CP1EE with 40 I / O, ie 24 inputs and 16 outputs, PLC is used here as a regulator to enable drivers dc motor is used as a regulator dc motor rotation direction to move pms. In the later rounds measured measurement value is varied. The results of these measurements can be read on the voltmeter and ammeter. Keywords: Driver Motor, DC Motor, Omron PLC CP1E, PMS.